Variety of Human Intelligence: Implications for Education and Self-Development - Maulidia, Maulidia; Mahmud, Salami; Pranajaya, Syatria Adymas; Agustina, Restika; Mahfud, Aris (Civiliza Publishing, Indonesia., 2025)
The conventional education system has been dominated by an approach emphasizing logical-mathematical and linguistic intelligence, as measured through IQ tests. The theory of Multiple Intelligences (MI) developed by Howard Gardner states that humans have eight types of intelligence: linguistic, logical-mathematical, musical, visual-spatial, kinesthetic, interpersonal, intrapersonal, and naturalistic. This study aims to examine how the theory of Multiple Intelligences can be applied in the education and self-development system to accommodate the diversity of individual potential optimally. This research uses a literature study method by examining various scientific sources related to MI, education, and self-potential development. The study results show that the MI-based learning approach encourages the application of more diverse, inclusive, and adaptive teaching strategies to students' learning styles. On the other hand, individuals who understand their intelligence profile can design appropriate learning strategies, choose educational and career paths more consciously, and develop potential in a balanced personal and social aspect. MI theory expands the scope of holistic education and becomes an important foundation in shaping reflective, independent, and competitive individuals.